(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
In 1952, the Venezuelan photographer, art historian and businessman Alfredo Boulton wrote an interesting essay that he entitled "Is photography an art?". He published this text in the heat of the massification of the technique that by then allowed millions of people to record through easy-to-use portable cameras moments of their daily life with a view to perpetuating the image of a being from the moment frozen in the shutter release. dear, a special date, a family gathering, the newly bought car or a tourist sight. The fact that the invention has become widespread and that the market has imposed its consumption does not deprive photography of the status of art.